Optimalisasi Pembinaan Anak Binaan Pemasyarakatan di LPKA Kelas 1 Kupang dalam Upaya Pencegahan Residivis - Alexander Esthario Martinus Corrua; Thelma Selly Marlin Kadja; Daud Dima Tallo (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this study is to analyze the optimization of fostering correctional children in LPKA Class 1 Kupang in an effort to prevent recidivism. The research method uses a qualitative method with an empirical legal research approach, sources and types of data in this study, namely primary data obtained from interviews and observations at LPKA Class 1 Kupang and secondary data obtained from literature studies, then processed by checking and correcting, then analyzed descriptively qualitative. Research results obtained: The optimization of the implementation of coaching for correctional foster children at LPKA Class 1 Kupang in an effort to prevent recidivism is carried out through personality coaching including spiritual guidance and counseling, fostering the nation and state, fostering arts and sports. While fostering independence is carried out through educational coaching, and skills coaching. In addition, reintegration and integration coaching is carried out including assimilation, conditional leave and parole. The implementation of the coaching process carried out on foster children at LPKA Class 1 Kupang is not free from various inhibiting factors including: infrastructure facilities and lack of quality human resources. Suggestion: It is expected that the LPKA Class 1 Kupang needs to improve adequate infrastructure, prepare the quality of human resources with various expertise that supports the implementation of the coaching process and cooperate with stakeholders and outside agencies, both government agencies and non-government agencies so that the coaching process can run optimally so that it can prepare foster children before returning to society.